2011
DOI: 10.1021/am101260a
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Preparation of High-Toughness Epoxy−SWNT Composite Materials

Abstract: Multicomponent nanocomposite materials based on a high-performance epoxy system and single-walled carbon nanotubes (SWNTs) have been prepared. The noncovalent wrapping of nitric acid-treated SWNTs with a PEO-based amphiphilic block copolymer leads to a highly disaggregated filler with a boosted miscibility in the epoxy matrix, allowing its dispersion without organic solvents. Although direct dispersion of acid-treated SWNTs results in modestly improved epoxy matrix mechanical properties, the incorporation of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
47
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 53 publications
7
47
2
Order By: Relevance
“…10(d)] showed actual ''break'' which appear as bright spots at the end of the nanotubes indicated by dotted red arrows. 15 Our results are consistent with Gonzalez et al; Gonzalez reported that the block copolymer (pluronic) wrapped SWCNTs when well dispersed in the epoxy matrix show as ''bright dots'' in the SEM images of fractured surfaces, which were interpreted by the authors as ''broken out'' CNTs and was noted as the reason for mechanical property improvement. However, the fractured sample of PSM processed specimen showed poor dispersion of nanotubes throughout the matrix and ''pull-out'' phenomena as seen by curled tubes in the image as indicated by solid red arrows.…”
Section: Full Papersupporting
confidence: 92%
See 2 more Smart Citations
“…10(d)] showed actual ''break'' which appear as bright spots at the end of the nanotubes indicated by dotted red arrows. 15 Our results are consistent with Gonzalez et al; Gonzalez reported that the block copolymer (pluronic) wrapped SWCNTs when well dispersed in the epoxy matrix show as ''bright dots'' in the SEM images of fractured surfaces, which were interpreted by the authors as ''broken out'' CNTs and was noted as the reason for mechanical property improvement. However, the fractured sample of PSM processed specimen showed poor dispersion of nanotubes throughout the matrix and ''pull-out'' phenomena as seen by curled tubes in the image as indicated by solid red arrows.…”
Section: Full Papersupporting
confidence: 92%
“…While there is a substantial amount of literature available for three-roll mill and US processing methods; limited literature is available on the use of high shear mixing methods, such as planetary shear mixing and microfluidics (MF), to deagglomerate CNTs in polymer nanocomposites. 15,17,18,34 In US, a pulsed ultrasound wave causes generation and collapse of submicron-sized bubbles of the resin mixture and thus deagglomeration of MWCNTs in the polymer matrix. However, processing of MWCNTs and polymer mixture using microfluidizer (MF) involves the fluid flowing at high velocities through microchannels of various geometries, and exposing the mixture to high shear stresses.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their good electrical properties, Ppy films show weak mechanical properties that can be improved by the addition of carbon nanotubes, as has been observed previously for several polymeric matrixes [14][15][16], thus obtaining a more resistant and durable support. Nanotubes also improve the electrical conductivity of polymer films, thus lowering the electrical resistance and impedance modulus of these materials [17].…”
Section: Introductionmentioning
confidence: 53%
“…However, two major problems such as lack of interfacial adhesion and poor dispersion of CNTs in the polymer matrix are often associated with these composites and limit their performance. [21][22][23] A good number of studies have been carried out based on the functionalization of CNTs to achieve uniform dispersion of the CNTs and optimum adhesion with the matrix. [24][25][26] The studies suggested that different functional modifications on CNTs play an important role to improve the compatibility between CNTs and the polymer matrix and also have effects on the structure and morphology of CNTs.…”
mentioning
confidence: 99%